Online Social Networking and Transnational-Competence Development Among International Students from Japan - Ngai, Phyllis (Journal of International Students, 2019)
Social media has become the window to the world near and far for international students. Apart from socializing and connecting with friends, what educational outcomes can be attributed to social networking sites (SNS)? This study examines the possibility that intercultural interactions on SNS can serve as a means of developing the transnational competence required for effective participation in an interconnected world. In this exploratory study, Japanese students studying in the United States participated in a mixed method study involving (1) a structured questionnaire about their perceived empowerment benefits of frequenting global SNS and (2) semi-structured interviews about the nature of these intercultural interactions on SNS. The implications of Facebook use for transnational-competence development are explored.